Pleural mesothelioma in a school teacher: asbestos exposure due to DAS paste - Barbieri, Pietro Gino; Somigliana, Anna; Girelli, Roberto; Lombardi, Sandra; Sarnico, Michela; Silvestri, Stefano (La Medicina del Lavoro, 2016)
Background: Malignant mesothelioma cases among primary school teachers are usually linked with asbestos exposure due to the mineral contained in the building structure. Among the approximately 12,000 cases of mesothelioma described in the fourth report of the National Mesothelioma Register, 11 cases of primary school teachers are reported, in spite of the fact that the “catalogue of asbestos use” does not describe circumstances of asbestos exposure other than or different to that due to asbestos contained in the buildings. Four cases in the Brescia Provincial Mesothelioma Register are identified as teachers, without this circumstance of exposure. Objectives: To characterize the asbestos concentration and fibre type retained in the lungs of a teacher reported as a new mesothelioma case and preliminarily classified as of unknown asbestos exposure. Methods: The mesothelioma case presented here was diagnosed at age 78 and malignant mesothelioma was confirmed at autopsy; the patient was interviewed directly for occupational history. Samples of lung parenchyma from necropsies were collected, stored and analyzed by scanning electron microscope (SEM) and samples of DAS paste were analyzed by SEM to detect asbestos fibre content. Results: It was possible to confirm past exposure to DAS paste in forming and finishing dry items and toys during school recreational activity almost every day from the mid-60s to about the mid-70s. Subsequent SEM analysis showed: i) chrysotile fibres were found in an old and unused pack of DAS paste; ii) a lung burden of 1,400 asbestos bodies, 310.000 total asbestos fibres (33% chrysotile, 67% amphibole) and 210.000 talc fibre per gr/dry lung tissue was detected from necropsies performed on the subject. These results seem to be in agreement with an occupational exposure to asbestos due to past use of DAS paste. After the investigation, this case was reclassified from “unknowun” to “ sure” occupational asbestos exposure. The occupational origin of the tumour was recognized by the Italian Workers’ Compensation Authority (INAIL). Conclusion: This case suggests i) the need to carry out any possible detailed studies of the circumstances and exposure sources whenever any mesothelioma case is classified as “asbestos exposure unknown”, according to the guidelines of the National Mesothelioma Register, ii) handling of DAS paste can be considered as sure asbestos exposure and iii) it should be borne in mind that mesothelioma cases can occur even after cumulative low, occupational exposure, even only to chrysotile.